Loss Accounting Practices among Takjil Sellers Grounded in Local Cultural And Religious Values - Thalib, Mohamad Anwar; Jusuf, Febiola; Tariki, Cindri; Pinga, Rika Oktaviyani (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2023)
This study aims to formulate loss accounting practices by takjil sellers based on local cultural values. This research uses a qualitative method. This study uses an Islamic ethnomethodological approach with five data analysis stages: charity, knowledge, faith, revelation, and courtesy. The results of the study found two ways for takjil sellers to avoid losses: distributing the remaining takjil merchandise for free to neighbors and family and giving bonuses. This loss accounting practice is conditional on the value of sharing, among others. Within the Islamic culture of Gorontalo, elders commonly impart this principle using the expression